More on Sibilant Devoicing in Spanish Diachrony: An Initial Phonetic Approach - Assumpció Rost Bagudanch (Languages, 2022)
The devoicing of sibilants took place in Early Modern Spanish, a phenomenon which has been considered problematic to account for due to its occurrence context (medial intervocalic position). Traditional explanations invoked Basque influence or a structural reorganization in search for a more balanced system. However, phonetically based reasons were proposed by some scholars. This research is a preliminary attempt to support these proposals with experimental data from a comparative grammar perspective. The Catalan sibilant system, which is very similar to the Medieval Spanish one, is acoustically and perceptively studied in order to investigate the acoustic cues of voicing and to determine if devoicing is possible. Results indicate that (a) voicing relies mainly in the proportion of unvoiced frames of the segments, on its duration, and, to a lesser extent, on its intensity; (b) sibilant devoicing occurs in all voiced categories; (c) auditorily, confusion between voiced and voiceless segments can be attested for every sibilant pair, and (d) the misparsings are more common in affricate and in palatal sibilants, [d͡ʒ] being the most prone to be labelled as unvoiced. These findings prove that the historical process in Spanish could have a phonetic basis.